Farmers' participation in agricultural research and extension systems - John, K. C.; Arora, S. K., 1948-; National Institute of Agricultural Extension Management (India) (New Delhi : Published for National Institute of Agricultural Extension Management, Hyderabad, by Concept Pub. House, 1997)
Review of reports from various parts of India.
Includes bibliographical references (p. [264]-266) and index.
Keywords: Agriculture -- Technology transfer -- India; Agricultural extension workers -- Training of -- India; Farms, Small -- Research -- India -- Citizen participation; Agricultural extension work -- India